2017
DOI: 10.1016/j.cis.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, stabilisation and encapsulation of bacteriophage for phage therapy

Abstract: Against a backdrop of global antibiotic resistance and increasing awareness of the importance of the human microbiota, there has been resurgent interest in the potential use of bacteriophages for therapeutic purposes, known as phage therapy. A number of phage therapy phase I and II clinical trials have concluded, and shown phages don't present significant adverse safety concerns. These clinical trials used simple phage suspensions without any formulation and phage stability was of secondary concern. Phages hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
303
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 396 publications
(342 citation statements)
references
References 229 publications
3
303
0
19
Order By: Relevance
“…Most phages only infect a small number of prevalent strains, thereby necessitating the use of phage cocktails to provide adequate therapeutic coverage. Phages incorporated in the cocktail may require tailored formulations to ensure adequate stability [96]. …”
Section: Discussionmentioning
confidence: 99%
“…Most phages only infect a small number of prevalent strains, thereby necessitating the use of phage cocktails to provide adequate therapeutic coverage. Phages incorporated in the cocktail may require tailored formulations to ensure adequate stability [96]. …”
Section: Discussionmentioning
confidence: 99%
“…Notably, sensitivity of phages to extreme pHs is typically investigated in vitro, thus excluding the potential impact of ionic composition and variety of organic (potentially protective) macromolecules present in the stomach. Therapeutic phage can be protected by encapsulation for example in polymeric microparticles, liposomes, or others . In vitro exposition of encapsulated phages to low pH clearly demonstrated that they were more resistant to acidic environment than free bacteriophages, some data indicate that encapsulation improve phage antibacterial activity in vivo .…”
Section: Entering the Systemmentioning
confidence: 99%
“…Therapeutic phage can be protected by encapsulation for example in polymeric microparticles, liposomes, or others . In vitro exposition of encapsulated phages to low pH clearly demonstrated that they were more resistant to acidic environment than free bacteriophages, some data indicate that encapsulation improve phage antibacterial activity in vivo . Thus, at least in phage strains that are highly sensitive to acidic environment, encapsulation may protect them during gut transit.…”
Section: Entering the Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The lysis from without is the most likely route of biocontrol of foodborne pathogens, mostly at usual cold storage temperatures (Sillankorva et al, ; Ferguson et al, ). However, under experimental conditions used in this study, it is unlikely that the reduction of E. coli on tomato surfaces could be caused by lysis from without, which this phenomenon usually occurs when the phage concentration is higher than the concentration of host bacteria (Malik et al, ).…”
Section: Resultsmentioning
confidence: 90%